Evaluation of low light intensity at three phenological stages in the agronomic and physiological responses of two rice (oryza sativa l.) cultivars (2013)
A study was carried out to assess the effect of two irradiance levels (100 and 50% natural light) at three different growth stages on yield and physiological characteristics of two rice cultivars (Fedearroz 50 and Fedearroz 733). The plants were exposed to low irradiance for 5 days consecutive by using black net cloth (about 50% of normal) at the panicle primordium, flowering and grain filling stages. The obtained results showed that the leaf chlorophyll content (SPAD readings) was higher in rice leaves under low irradiance. The chlorophyll content from the shade treatment apparently remained constant until the grain filling phase, then decreased slightly in the 'F50' rice plants and remarkably in the 'F733' plants. Stomatal conductance (gs) was negatively affected by shading, with the effect being more adverse in the 'F733' plants. At the flowering and grain filling phases, grain yield was reduced by the low light treatments by around ~20% in the 'F50' plants. While, in 'F733', they were only affected by shading at the grain filling stage, causing a decrease of around 25%. These results seem to indicate that ‘F773’ may have a better capacity for partitioning dry matter than ‘F50’ in spite of the fact that the gas exchange characteristics were conditioned by low irradiance conditions at the reproductive and ripening phases.